GLOBAL SECURITY ISSUES: TACKLING MIGRATION AND REFUGEE CRISES (Security Dialogues, 2024)
Global security and migration are closely related to each other and mutuallyinfluence the situation in the world. Migration can be both a cause and a consequence ofthreats to global security. One of the main reasons for migration is instability and conflictin countries, which can lead to security threats both within and outside the country.Armed conflicts, terrorism, human rights violations, deteriorating economic situation andenvironmental disasters can force people to leave their homes and seek a better life in othercountries. On the other hand, mass migration can cause tension in receiving countries, whichcan lead to social and economic problems, as well as security threats. Illegal and uncontrolledmigration can contribute to crime, human trafficking and in some cases terrorist attacks.From an economic perspective, migration may potentially lead to significant negative effectssuch as increased unemployment among natives, increased shadow economy and may putupward pressure on housing costs. To ensure global security, it is necessary to develop acomprehensive approach to migration management that will consider the interests of allparties. This includes strengthening international cooperation, tackling the root causes ofmigration and ensuring sustainable development in source countries. Thus, the connectionbetween global security and migration highlights the need for joint efforts by countries andinternational organizations to address the complex challenges posed by these phenomena.
Keywords: Global Security, Migration, Economy, Terrorism